Abernethy Malformation and the Spectrum of Imaging Findings: A Case Report - Gangadhar, K; Nair, SV; Sunnapwar, A; Chintapalli, KN (Nepalese Journal of Radiology, 2014)
Congenital extrahepatic porto systemic shunt (CEPS) is a rare condition in which the porto mesenteric blood drains into a systemic vein, bypassing the liver through a complete or partial shunt. It is commonly associated with multiple congenital anomalies. A diagnosis of Abernethy malformation is made by non-invasive cross-sectional imaging techniques such as Doppler ultrasound, CT or MRI, which show the shunt and intrahepatic portal vein branches. We report a case presenting with psychological issues, systemic hypertension, upper extremity deformities, liver lesions and portal hypertension. Usually the patients are diagnosed in childhood, in our case the patient is a middle aged woman. This case report shows the importance of imaging in diagnosis of this condition and presentation of the patient with portal hypertension which is rare. DOI: http://dx.doi.org/10.3126/njr.v3i2.9622 Nepalese Journal of Radiology Vol.3(2)July-Dec, 2013: 97-102